Impact of land degradation in Bangladesh : changing scenario in agricultural land use - Karim, Z.; Iqbal, M. Anwar; Rahman, Mustafizur (Soils publication ;, 2001)
Based on presentations at a workshop organized by Bāṃlādeśa Kr̥shi Gabeshaṇā Kāunsila on December 27, 1998.